Public Administration and Panchayati Raj Institution: Examining the Role of Public Administration in the Panchayati Raj System (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The public authorities and the Panchayati Raj Institution will be analyzed in this article. The detailed execution of public law is the public administration. Public administration is every specific application of law. Public administration is a collaborative effort of a group of persons pursuing a common goal in the management of public affairs. In two senses: narrower meaning and broader sense, public administration has been employed. Public administration in the broader meaning covers execution activities solely. While the Panchayati Raj system in India is commonly referred to in 1992, it is based on the South Asian panchayat traditional structure. It should not be confused with the extra-constitutional khape (or caste panchayat) panchayati prevalent in several regions of North India that is the current panchayati raj and its gramme panchayat. During the formalisation of the panchayati raj system in 1992, several Indian committees were investigating various approaches for more decentralized administrations to be implemented before that transition. It would have been a decentralized type of administration where each village would take responsibility for its own affairs. Mahatma Gandhi supported Panchayati raj as the foundation for the political system of India.